Analysis on EZH2: mechanism identification of related CeRNA and its immunoassay in hepatocellular carcinoma - Haoran Zhao; Haishi Liu; Wenli Kang; Chao Zhan; Yingchun Man; Tong Qu (BMC, 2023)
Abstract Objective To screen the possible potential signaling pathways related to enhancer of zeste homolog 2 (EZH2) based on ceRNA mechanism, and to analyze the correlation between E2H2 and depths of various immune cell infiltration depths. The relationship between different immune checkpoints were also analyzed. Methods First, the expression of EZH2 in pan-cancer (18 malignancies) was analyzed with the TCGA database. Hepatocellular carcinoma (HCC) tissues of 374 cases and normal tissues of 50 cases were analyzed in terms of the differential expression, overall survival (OS) and progression-free-survival (PFS). Then, we conducted GO and KEGG enrichment analysis on target gene. We also analyzed mRNA-miRNA and MicroRNA (miRNA)- long non-coding RNA (lncRNA) correlation with starbase databse, so as to determine the potential ceRNA mechanism associated with EZH2. Finally, immunoassay and drug-sensitivity analysis of EZH2 was performed. Results Seven potential EZH2-related ceRNA pathways were screened out, namely lncRNA: Small Nucleolar RNA Host Gene 1 (SNHG1), SNHG 3, and SNHG 6-miR-101-3p-EZH2; and lncRNA: Long Intergenic Non-Protein Coding RNA 1978 (LINC01978), SNHG12, Ring Finger Protein 216 Pseudogene 1 (RNF216P1), and Coiled-coil Domain Containing 18 Antisense RNA 1 (CCDC18-AS1)-let-7c-5p-EZH2. Finally, 4 potential EZH2-related ceRNA pathways were identified through qPCR.According to immune correlation analysis, EZH2 may be positively correlated with T cells follicular helper, T cells Cluster of differentiation (CD)4 memory activated, Macrophages M0, and B cells memory (P < 0.05, cof > 0.2); while be negatively correlated with T cells CD4 + memory resting (P < 0.05, cof < -0.2). And EZH2 is positively correlated with Programmed Cell Death 1 (PDCD1) (R = 0.22), CD274 (R = 0.3) and Cytotoxic T-Lymphocyte Associated Protein 4 (CTLA4) (R = 0.23). According to drug sensitivity analysis, patients in the high expression group were more susceptible to the effects of various drugs including Sorafenib, 5-Fluorouracil, Doxorubicin, Etoposide, Paclitaxel, and Vinorelbine than those with low expression. Conclusion This study revealed seven potential pathways of Enhancer of Zeste Homolog 2 (EZH2)-related ceRNA mechanisms: lncRNA (SNHG3, 6) -Mir-101-3P-ezh2; lncRNA (SNHG12, RNF216P1)-let-7c-5p-EZH2. We also analyzed the immunity and drug sensitivity of EZH2. Our study proves that EZH2 still has great research prospects in HCC.